Effect of Weed Management Practices on Weed Dynamics, Yield and Economics of Sweet Potato ( Ipomoea batatas L.) - Singh, R S; Singh, P P; Narayan, A (JOURNAL OF ROOT CROPS, 2017)
An experiment was conducted to find out the most suitable weed management practice for weed management in sweet potato during 2015-16 at Agricultural Research Farm, Dholi of Dr. Rajendra Prasad Central Agricultural University, Pusa (Bihar) under sandy loam soil. It was found that the herbicide Quizalofop-p-ethyl alone or in combination with other herbicides performed better than all other herbicides tested. It may be due to its better efficacy towards controlling narrow leaved weeds particularly against the most dominant weed of the field Sorghum halepanse . The most effective combination of herbicides was pendimethalin followed by quizalofop-p-ethyl (T 7 ) which may be due to weed control right from the early stage up to about a month by the application of pendimethalin and thereafter control of most dominating and vigorous weed Sorghum halepanse by the application of quizalofop-p-ethyl. Although lowest weed population and weed dry matter at 30 and 60 days after planting were recorded under T 10 (Hand weeding twice at 20 & 40 days after sowing) and was significantly superior than all other treatments, it could not achieve highest net return and B : C ratio even after realizing highest tuber yield (20.3 t ha -1 ). Best weed index (9.36 %) was recorded by the treatment combination of pendimethalin (T 1 ) followed by quizalofop-p-ethyl (T 7 ) and it was equally good with hand weeding twice (T 10) with respect to tuber yield. Significant highest net return ( ` 115226 ha -1 ) was recorded by T 7 than all other treatments but was found on par with T 10 ( ` 111826 ha -1 ). B : C ratio recorded by T 7 (3.60) was significantly superior than the other treatments. Highest weed population, weed dry matter, weed index and lowest tuber yield, net return and B : C ratio were recorded under control treatment.